A Conversation between Ted Jacobs and Wendy Olesker. Issue 6 (18th August 2022) - Jacobs, Ted; Olesker, Wendy
ABSTRACT: Ted has been teacher, colleague, and friend to me throughout my professional life. There was something about Ted's person that resonated with me. I felt his presence when I began training at Albert Einstein College of Medicine, where I did my internship and clinical fellowship, and again as I was going through training at NYPSI. Once I graduated, I had the good fortune of being invited to a study group with Ted, Charlie Brenner, and many other senior analysts. I was most impressed with his ways of thinking, his humanity, which came across vividly in his work and in his responses to others. He had an openness and dedication to finding ways to reach each individual patient. I especially admired his emphasis on turning to the evidence from the patient, and his focus on really helping his patients with what was central to them, not having to stick to analytic rules. He was courageous in his willingness to present his careful analytic work when his focus on countertransference was not considered appropriate at the time, with much backlash from others. In terms of Ted's importance to psychoanalysis, starting in the 70ʹs, he focused in on an area of psychoanalysis that was quite undeveloped at the time – the analyst's use of his self, except for a few strong voices from the Kleinians (Heiman, 1950, Racker, 1953), though of course many others later. Ted could see the limitation of focusing only on the transference, omitting countertransference. He focused on "what's happening between us" before any concept of the "analytic third" or "co construction" had been born. So much focus was on the intrapsychic – the only focus of a "true" analyst, at a time when the interpersonal was viewed as "nonanalytic." He brought his analytic lens, studying the analytic data in the countertransference, to the benefit of the psychoanalytic community, a focus quite different from relational analysis and interpersonal analysis. His influence on my own work was powerful. The shared background of training in a place with many gifted and talented people, who all were seriously involved in trying to learn analysis and apply the work to patients, but with an openness to new ideas, to valuing the data from the patient above loyalty to a particular theory, the lens on one's own feelings, thoughts, fantasies, attitudes to facilitate the most full understanding of the patient, all have enriched my understanding and appreciation of the analytic process.